Cost analysis and economical suitability of prefabricated concretestructures in building construction - Fatima Naz; Safeer Ahmed Abro; Nafees Ahmed Memon; Noman Ahmed (Penerbit Universiti Kebangsaan Malaysia, 2023)
Construction industry of Pakistan has a great contribution in uprising the GDP of the country. When compared with the construction industries of some developed countries of the world it still lacks in utilizing the modern methods of construction. Most of the organizations are relying on traditional ways of construction and are not ready to equip themselves with the advanced techniques of construction that may help them do their projects more effectively and efficiently. Prefabrication is the future of modern and sustainable construction which can maximize the capability of constructing the structures without compromising not only the time, cost and quality of project but also the environment. Prefabrication is rapidly increasing in construction, and previous researchers have identified various positive impacts of prefabrication on projects. However, prefabricated construction is less preferred over traditional methods of construction in Pakistan. Therefore, a comparison is required between conventional RCC building and a prefabricated (precast RCC) building to unearth the potential benefits of adopting prefabrication on overall cost of project. To achieve this, a BIM based multi-dimensional model of conventional and prefabricated building is developed using Autodesk Revit. A detailed comparison between both the methods of construction with respect to material, labor, transportation and time made the benefits of prefabricated construction clear over conventional construction. Prefabrication method is 84% faster and costs about 13.46% less than conventional method of construction. This comprehensive contrast will help to better understand and encourage the construction industry to move towards the prefabricated construction.